The viewpoints of medical sciences wealth creators regarding the wealth creation strategies and path in medical sciences universities - Atefeh Zabihi Zazoly; Shoaleh Bigdeli; Zohreh Sohrabi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In the recent years, the wealth creation of educational institutions has attracted an enormous attention in different countries. Exploring experiences of these institutes help to improve the wealth creation of universities. In this regard, this study was an attempt to explain the viewpoints of the wealth creators of medical sciences regarding wealth creation strategies and define the general path of wealth creation in medical sciences universities. MATERIALS AND METHODS: This qualitative study was conducted at Iran University of Medical Sciences, Tehran, Iran, in 2021. Participants were the experienced knowledgeable wealth creation experts. Fourteen semi-structured interviews were conducted to reach data saturation. Interview guided questions were about strategies and paths of wealth creation followed by probing questions. Data were analyzed using conventional qualitative content analysis. RESULTS: Data analysis showed that the most important strategies were related to nine extracted categories of "the productions", "contracts and relations", revising, predicting and foresight" -, "education", "research", "healthcare services", " interdisciplinary fields between Information Technology (IT) and health-care", " saving and maintenance", and "altering the procedure of the wealth accelerator centers." In general, wealth creation path in medical sciences includes six main categories. CONCLUSIONS: The result of this study provide an opportunity for educational policy-makers and authorities to improve wealth creation in medical universities. Especially, accentuated by the COVID-19 pandemic, to consider the interdisciplinary fields between IT and health-care and integrating technology to the various categories of medical sciences are absolute needs.